A quantitative study of financing efficiency of low‐carbon companies: A three‐stage data envelopment analysis. (18th February 2019) - Liu, Xun; Yu, Xiaoliang; Gao, Simon
Abstract: This study set out to evaluate the financing efficiency of low‐carbon companies. Applying a three‐stage data envelopment analysis with the data from 85 listed companies in China's low‐carbon industries over the period 2011 to 2017, this study has found that the overall financing efficiency of low‐carbon companies was relatively high, and the pure technical efficiency was quite steady over the period. The overall financing efficiency of these low‐carbon companies on average tended to change with the scale efficiency. This study has also shown that the scale efficiency was the main constraint influencing the financing efficiency of low‐carbon companies in China over the period. Our results are robust and have significant implications for policy makers and corporate managers.